Intralingual and intersemiotic translation for accessibility in educational and social environments - focus on legal language - Canepari, Michela (Comparative Legilinguistics, 2023)
Over the years, what is normally referred to as visual law has increasingly developed and some scholars have been tentatively experimenting with legally binding comics, although in very limited numbers. This article posits itself as part of that tradition, while taking the issue a step forward, further developing the academic discussion around the notion of accessibility in legal language and emphasising the importance that different forms of translation can assume in this context. The article thus discusses the impact that intralingual and intersemiotic translation can have in both “educational” and more “social” contexts, finally providing two brief examples of how these forms of translation can render legal discourse more accessible and understandable to a great variety of receivers, regardless of their age, level of education, cultural origin, etc.